Nonpharmacological interventions for cancer-related fatigue: A comprehensive literature review - Shufang Zuo; Hui Cheng; Ziyu Wang; Tingting Liu; Si Chen; Li Tian; Lu Lin (Elsevier, 2023)
Cancer-related fatigue (CRF) is a prevalent and debilitating side effect of cancer treatment that can persist for years posttreatment, significantly impacting patients' quality of life. Given the limited efficacy of pharmacological treatments, nonpharmacological interventions are gaining attention as effective management strategies for CRF. This review aims to provide an overview of the most common nonpharmacological interventions for CRF management, including exercise therapies, psychosocial interventions, sensory art therapy, light therapy, nutritional management, traditional Chinese medicine therapies, sleep management, combination therapy, and health education. By synthesizing the findings of high-quality literature, this review presents the definition of each therapy, along with their advantages and disadvantages in treating patients with CRF. Additionally, it addresses the role of oncology nurses in the nonpharmacological management of CRF. In summary, this review aims to inform oncology nurses about the prevalent nonpharmacological interventions for CRF and explore their clinical application to facilitate the development of effective CRF management strategies in clinical practice.